All Days 2004
DOI: 10.2118/87430-ms
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Carbonate Scale in Oil Producers from High Temperature Reservoirs

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractCalcium carbonate scale is a common problem in the oil industry leading to reduced well performance and obstruction of the safety valves. Recent field experiences indicate that scaling may be a problem at lower Saturation Ratio (SR) than earlier anticipated. In a high pressure, high temperature Scale Cell crystal growth in synthetic formation water has been studied. Induction times and growth rates have been determined using a microscope cell. The results hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Often used critical values for calcite are an SR between 2 to 3, for BaSO 4 an SR between 5 and 10 and for SrSO 4 an SR of 2 to 5. Ramstad et al 3 have recently shown that the critical SR for calcite is much lower than 2 for wells where the temperature is >100 o C.…”
Section: Scaling Calculationsmentioning
confidence: 99%
“…Often used critical values for calcite are an SR between 2 to 3, for BaSO 4 an SR between 5 and 10 and for SrSO 4 an SR of 2 to 5. Ramstad et al 3 have recently shown that the critical SR for calcite is much lower than 2 for wells where the temperature is >100 o C.…”
Section: Scaling Calculationsmentioning
confidence: 99%
“…Relatively high reservoir temperature (124 °C) combined with pressure drop in the wellbore has caused calcium carbonate scale to form in the upper tubing, affecting operation of DHSV (540 m MD) (Ramstad et al, 2005). The Oseberg Øst field consists of deviated and horizontal wells producing from the Brent group reservoirs and the drive mechanism is gas and water injection (Utsira aquifer and produced water).…”
Section: Scaling Of Production Intervals Due To Incorrect Inhibitor Pmentioning
confidence: 99%
“…SR of 2 at 98°C. 4 Other work suggests that an SR of 5 may be required for calcium carbonate precipitation at 80°C, whereas this drops to 1.2 at 150°C. 5 Thus given that a brine system is at equilibrium in the reservoir, during production at elevated temperatures only very small perturbations in the equilibrium of the brine chemistry, by pressure changes during production or re-distribution of water and / or carbon dioxide between the different phases, can rapidly lead to precipitation of scale, whereas such small changes in more a less severe (lower temperature) environments may not represent a scaling problem.…”
Section: Introductionmentioning
confidence: 98%